Sequence Stratigraphy of the Cenomanian - early Turonian Cycle in the Selected wells, Southeastern Iraq - Al-Zaidy, Aiad Ali Hussien; Al Shwaliay, Hussein Shwayel Aoudeh (Iraqi Journal of Science, 2018)
Sequence stratigraphic cycle of Cenomanian-early Turonian is composed of (Ahmadi, Rumaila, and Mishrif) formations, which is bounded at top and base by unconformity surfaces. The lithofacies of this cycle in the southern Iraq indicate a normal lateral change facies from shallow water facies through deeper water and open marine sediments, Ahmadi Formation (early Cenomanian) characterized by open marine sediments during the transgressive conditions, and passes up into deep basinal sediments (Rumaila Formation) by conformably surface. Rumaila Formation (middle Cenomanian) was deposited in the deeper part of the intrashelf basin, which comprises of a mainly basinal sediments, and includes an abundant of open marine fauna supportive of middle Cenomanian age. Rumaila Formation is represented time equivalent basin to the Mishrif Formation, and they deposited during highstand system tract. The Cenomanian-early Turonian cycle can be subdivided into three medium sequences displays coarsening upward cycles (Mishrif A, Mishrif B, and Mishrif C), which comprises of one reservoir pay zone dominated by rudistid packstone to grainstone or rudistid biostrome facies separated by barriers (dense non- porous) units (CR I and CR II). The microfacies analysis of the study wells assisted the recognition of five main environments (open marine, basinal, shallow open marine, Rudist biostrome, and lagoon).